Factors that affect the appropriation, and practical and massive application of the integrated pest management in coffee. Their implications for a strategy of diffusion. The case of MIP of Nicaragua - Gómez Delgado, D.M. (1998)
14 fig. 3 tab. Bib. p. 92-94.